Continuous scanning trials:Transitioning through the attractor landscape. (1st January 2016) - Kennedy, Deanna M.; Wang, Chaoyi; Panzer, Stefan; Shea, Charles H.
Highlights: Participants were asked to transition from in-phase to anti-phase in 1° increments within a trial. Participants were very effective in navigating through the relative phase landscape. The results indicate integrated displays greatly increase performers' bimanual capabilities. Abstract: Bimanual 1:1 coordination patterns other than in-phase (0°) and anti-phase (180°) have proven difficult to perform even with extended practice. The difficulty has traditionally been attributed to phase attraction that draws the coordination between the limbs towards the bimanual patterns of in-phase and anti-phase and variability associated with the activation and associated proprioceptive signals of non-homologous muscles via crossed and uncrossed cortical pathways. However, recent experiments have demonstrated that a wide range of relative phase and multi-frequency coordination patterns can be effectively produced with only a few minutes of practice when Lissajous or online relative phase information is provided. The present experiment was designed to determine if participants provided Lissajous feedback comprised of continuously transitioning relative phase goals could be effectively performed as the participant navigates through the attractor landscape. The results clearly indicated that participants can effectively produce a large range of supposedly unstable coordination patterns (between 0° and 180° in 1° increments) after only a few minutes of practice. These findings clearly indicate that the perception-action system is fully capable of effectively producing and transitioning through a wide range of bimanual coordination patterns and that the reason for the failure to produce these patterns in previous experiments resides in the perceptual information and attentional requirements typically found in experimental testing environments.